Technological change and factor substitution in milk production* - KUMAR, VINOD (The Indian Journal of Animal Sciences, 2014)
The present study was conducted during 1990-91 to examine the effect of technological change on factor substitution in milk production in Meerut district of Uttar Pradesh. Data on consumption of green fodder and concentrate were collected for rainy, winter and summer seasons by survey method for the year 1990-91. Linear, Cobb Douglas and Quadratic type of milk production were fitted. The Cobb Douglas milk production function was the most suitable for further economic analysis. The milk isoquant for a specific level of milk yield were obtained using Cobb Douglas milk production functions separately for buffaloes, crossbred and local cows. The marginal rates of substitution of green fodder for concentrate and isoclines were also obtained. At a given price ratio (0.04) for every 2 kg enhancement in milk yield the rate of increase in green fodder was 4 to 6 kg in buffaloes, 11 to 12 kg in local cows and 2 to 3 kg in crossbred cows (new dairy technology). The rate of concentrate increased at increasing rate initially, thereafter it increased at declining rate. The study revealed that the rate of substitute of concentrate by green fodder was the highest for buffaloes followed by local cows and crossbred cows. The results also revealed that there is a good scope for substitution of concentrate by green fodder in old milk production technology (buffaloes and local cows) even at a higher level of milk yield, while it was possible only at lower level of milk yield in case of new dairy technology (crossbred cows).